Assessment for inclusion: rethinking contemporary strategies in assessment design. Issue 2 (17th February 2023) - Tai, Joanna; Ajjawi, Rola; Bearman, Margaret; Boud, David; Dawson, Phillip; Jorre de St Jorre, Trina
ABSTRACT: Assessment has multiple purposes, one of which is to judge if students have met outcomes at the requisite level. Underperformance in assessment is frequently positioned as a problem of the student and attributed to student diversity and/or background characteristics. However, the assessment might also be inequitable and therefore exclude students inappropriately. To be inclusive, assessment design needs to be reconsidered, and educators should look beyond simplistic categories of disability or social equity groups, towards considering and accounting for diversity on many spectra. This article introduces the concept of assessment for inclusion, which seeks to ensure diverse students are not disadvantaged through assessment practices. Assumptions in assessment design are problematised from this point of view, and three central concerns relating to assessment traditions, assessment expectations, and academic integrity are interrogated. Contemporary design strategies of authentic assessment, programmatic assessment, and assessment for distinctiveness are then harnessed to illustrate approaches to assessment for inclusion. Assessment for inclusion therefore builds on the synergies between inclusive practice and good assessment design.